Bacterial phenotype dependency from CO2 measured by Raman spectroscopy - Wichmann, Christina; Bocklitz, Thomas; Roesch, Petra; Popp, Juergen (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2021)
In recent years, Raman spectroscopy has become an established method to study medical, biological or environmental samples. Since Raman spectroscopy is a phenotypic method, many parameters can influence the spectra. One of these parameters is the concentration of CO2, as this never remains stable in nature, but always adjusts itself in a dynamic equilibrium. So, it is obvious that the concentration of CO2 cannot be controlled but it might have a big impact on the bacteria and bacterial composition in medical samples. When using a phenotypic method like Raman spectroscopy it is also important to know the influence of CO2 to the dataset. To investigate the influence of CO2 towards Raman spectra we cultivated E. coli at different concentration of CO2 since this bacterium is able to switch metabolism from aerobic to microaerophilic conditions. After applying statistic methods small changes in the spectra became visible and it was even possible to observe the change of metabolism in this species according to the concentration of CO2.
CRIS-Team Scopus Importer:2023-04-20
Keywords: CO; E. coli; Lung microbiome; Metabolism; Raman spectroscopy; Respiration